PROSES ADSORPSI SENYAWA LINIER ALKILBENZENE SULFONAT (LAS) MELALUI ARANG AKTIF KULIT UBI KAYU - Rosliana Lubis; Tsara Atsary (BIOLINK (Jurnal Biologi Lingkungan Industri Kesehatan), 2015)
This research aims was to analyze the potential of activated charcoal leather cassava in the adsorption process linear compounds alkilbenzene sulfonate (LAS) contained in the liquid waste household detergents. Stages of the study consisted of charcoal formation process of the skin of cassava through the combustion process of pyrolysis, charcoal leather activation process cassava, and the compound adsorption process linear alkyl sulfonate (LAS) contained in the liquid waste household detergents. The results showed that activated charcoal is formed from leather waste cassava LAS have the ability to adsorb the compounds contained in domestic wastewater. Treatment optimum adsorption occurs at a concentration of activated charcoal leather cassava 4 grams and a contact time of 20 minutes.